Analytical and subjective interpretation of thermal comfort in hospitals: A case study in two sterilization services. Issue 7 (2nd April 2016) - Carvalhais, Carlos; Santos, Joana; Vieira da Silva, Manuela
ABSTRACT: Hospital facilities are normally very complex, which combined with patient requirements promote conditions for potential development of uncomfortable working conditions. Thermal discomfort is one such example. This study aimed to determine levels of thermal comfort, sensations, and preferences, from a field investigation conducted in two sterilization services (SS) of two hospitals from Porto and Aveiro, Portugal. The analytical determination and interpretation of thermal comfort was based upon assumptions of ISO 7726:1998 and ISO 7730:2005. The predicted mean vote (PMV) and predicted percentage of dissatisfaction (PPD) indices were obtained by measurement and estimation of environmental and personal variables, respectively, and calculated according to ISO 7730 equations. The subjective variables were obtained from thermal sensation (subjective PMV) and affective assessment (subjective PPD), reported by a questionnaire based upon ISO 10551:1995. Both approaches confirmed thermal discomfort in both SS (codified as SS1 and SS2). For all areas, PMV and PPD exceeded in all periods of the day the recommended range of –0.5 to +0.5 and <10%, respectively. No significant differences were found between day periods. The questionnaire results showed that SS2 workers reported a higher level of thermal discomfort. There were no significant differences between PMV and thermal sensations, as well as between PPD and affective assessment. The PMV/PPD model was found suitable to predict thermal sensations of occupants in hospital SS located in areas with a mild climate in Portugal.